Psychosocial Factors and Mental Disorders in Healthcare Workers Facing Covid-19 - Messias, João Carlos Caselli (2023)
This study aimed to assess psychosocial risk factors and Minor Mental Disorders (MMD), as well as the possible effects of the pandemic on 85 healthcare workers working in two hospitals in the city of Campinas, SP (Brazil). This was an exploratory-descriptive, cross-sectional study, conducted through convenience sampling, utilizing an online platform. The study employed a Sociodemographic and Occupational Questionnaire, as well as the SRQ-20 and COPSOQ II instruments. The results indicated a risk level for emotional demands, cognitive demands, and work pace. Suspicion for MMD was 65.9%, being moderately associated with Quantitative Demands and Emotional Demands. The group that perceived a worsening of the work routine had a significantly higher score in the suspicion of MMD, as well as being more subject to emotional demands, cognitive demands, Demands for hiding emotions and quantitative demands. It is concluded that healthcare professionals who worked on the front line in the Covid-19 pandemic were subject to several psychosocial risk factors for the development of MMD. Awareness of these factors enhances the understanding of the challenges and needs faced by this group of professionals. It is hoped that his contribution will support future studies aimed at further exploring these issues.